Assessment of marine litter interaction in cetaceans stranded along the Italian coastline and the Adriatic Sea - Pietroluongo, Guido; Centelleghe, Cinzia; Baini, Matteo; Cocumelli, Cristiano; Casalone, Cristina; Corazzola, Giorgia; Di Francesco, Gabriella; Di Nocera, Fabio; Di Renzo, Ludovica; Đuras, Martina; Fossi, Maria Cristina; Gavaudan, Stefano; et al. (Frontiers in Marine Science, 2025)
Marine litter represents a growing threat to marine biodiversity, particularly to cetaceans, yet its impacts on these sentinel species remain insufficiently quantified. This study provides the first comprehensive, transboundary assessment of litter ingestion in stranded cetaceans along the Italian coastline and across the wider Adriatic basin, including Croatia and Slovenia, between 2009 and 2023. Through harmonized post-mortem examinations, and focusing on the period of consistent data collection and analysis (2009-2023), this study documented plastic litter ingestion in 2.9% of necropsied cetaceans in Italy and 3.7% in the broader Adriatic subregion, with sperm whales (Physeter macrocephalus) showing the highest frequency (50% FO) and susceptibility. In 11 cases, ingestion was associated with health deterioration and mortality. The most commonly ingested items were plastic sheets and fragments. The Italian Adriatic subregion emerged as a hotspot for plastic interactions, reflecting regional hydrodynamics and anthropogenic pressures. Applying criteria from regional and international frameworks, the results showed that 60% of P. macrocephalus had ingested more than 1 kg of plastic, with 40% exhibiting harmful effects. These data provide baseline values that can serve as reference points for proposing thresholds to achieve Good Environmental Status under the Marine Strategy Framework Directive. Despite these results supporting the use of sperm whales as suitable sentinel species for monitoring macroplastic pollution, the available data are limited to Italy and influenced by distributional patterns and unusual mortality events. A combined approach, where T. truncatus is monitored for its broad spatial representativeness and P. macrocephalus for its ecological susceptibility, may be a useful strategy to guide further research and inform management measures in the future. These findings underscore the need for standardized monitoring protocols, enhanced cross-border data sharing, and policy measures to mitigate plastic impacts. This work provides crucial baseline knowledge for conservation planning and reinforces the role of cetaceans as indicators of ecosystem health in the Mediterranean.